Optimalisasi Manajemen Pembelajaran Projek Berbasis STEAM-AI untuk Meningkatkan Kreativitas Guru SMP - Syahputri, Nita; Sya'dian, Triadi; Suwanto, Fevi Rahmawati; Ramadhani, Rahmi; Lahilote, Abqoriy Hisan; Niami, Tamama Alvin (JPM: Jurnal Pengabdian Masyarakat, 2025)
Strengthening teachers’ capacity in managing project-based learning is an urgent need in 21st-century education, particularly in the context of integrating STEAM and artificial intelligence (AI). This community service program was implemented to address the challenges faced by teachers at SMP Negeri 14 Binjai, who continue to experience difficulties in managing project-based learning and have yet to fully optimize the integration of creativity and technology. The objective of this activity was to enhance teachers’ competence in designing and implementing innovative STEAM-AI-based learning through a participatory approach. The program’s partners were teachers of SMP Negeri 14 Binjai, organized under the Teacher Learning Community, with a total of 30 participants. The implementation method was carried out in three stages: preparation, which included needs assessment and module development; execution, which involved training, workshops, and classroom mentoring; and evaluation, which consisted of pre- and post-tests, assessment of lesson design products, and participant reflections. The results showed an improvement in teachers’ understanding of STEAM-AI concepts and project management skills, as reflected in increased test scores and higher-quality lesson designs, reaching 86.7%. Additionally, the program produced other outputs, including the development of a supporting application for implementing STEAM-AI-based project learning, namely the eSTEAM-AI application, and the establishment of a community of practice that serves as a sustainable platform for innovation in schools. Thus, this community service program successfully contributed to enhancing teacher professionalism while supporting the educational transformation in Binjai toward more creative, collaborative, and globally relevant learning.